Tinjauan Kritis terhadap Gereja di Era Digital dan Pelayanan bagi Lanjut Usia di Masa Pandemi Covid-19 - Akwila Priska Ibu (Tumou Tou, 2022)
This paper aims to explain and analyze the services received by the elderly in the midst of a pandemic at this time in the digital era. The method in writing this article is literature by using reference books and journals as well as some field data related to this topic. As for the background of this paper, the increasingly rapid technological advancements in this digital era, requires everyone to adapt to it. Communion in the church is very important for the elderly. With these developments, finally the elderly learn to be able to accept existing technological developments. So that they can live out their longing for fellowship in the church. Church services that are carried out in this digital era have become a big task for the church. The church has a duty to adapt in terms of technology. Thus, technology enables everyone, including the church, to be able to run services side by side with today's technology media.